Development of ceramic cutting insert of aluminium oxide (Al2O3) and titanium carbide (TiC) for machining steel - Isa, Mohd. Akmal (2007)
Manufacturing of cutting inserts was considered difficult and required extensive as to fulfill the industries needed. Several methods were used in manufacturing the insert and one of them is pre-forming process of mix powder parts prior to densification by sintering. Isostatic pressing can be applied at very high pressure uniformly in all directions producing parts, which are consistent in density throughout their cross sections and highly accurate as compared to those produced uniaxially. As a result more uniform density and greater compaction of insert was produced. In research, the combination of alumina oxide and titanium carbide powders was this pressed and then sintered in a vacuum sintering furnace. The effect of the titanium carbide content in the alumina has study after completion of sintering process. The effect on the shrinkage, hardness, density and surface roughness of the inserts were also investigated. The temperature of sintering process was also investigated. Through this research, relationship between process parameters and the content of titanium carbide powder were established and used to produce ceramic inserts. In addition machining tests were concerned out on steel to evaluate the tool life of the inserts.